Pengenalan Gangguan Reproduksi Anak Pria Pra-Pubertas di Kelurahan Meras Kecamatan Bunaken, Kota Manado - Maabuat, Pience Veralyn; deQueljoe, Edwin (The Studies of Social Sciences, 2021)
Disorders or abnormalities of sexual differentiation and development in men and women began to be known when the child entered the prepubertal period. For boys, abnormalities include cryptorchidism, hypospadias, congenital bilateral absence of the vas deferens, and pseudohermaphroditism. The prepubertal period is the period that begins at the end of childhood called prepuberty, also known as the maturation stage where at this stage secondary sex characteristics begin to appear and the reproductive organs in boys have begun to develop perfectly. For this reason, it is necessary for early recognition through the transfer of knowledge regarding reproductive organs, especially known by parents, so that they can give attention to the health condition of children in the family and of course can determine steps for early countermeasures if a disorder is found in the child's reproductive organs. Partners who participated in this activity were community members in Meras Village, Bunaken District, who had children from prepuberty to teenage. The purpose of this activity is to increase public knowledge about reproductive health in boys prepubertal. The results obtained were an increase in knowledge through given tests before and after the transfer of knowledge, and the results of the free examination carried out did not find abnormalities in the sample children.Keywords: Disorders; reproduction; cryptorchidism; hypospadias; Meras AbstrakGangguan atau kelainan diferensiasi dan perkembangan seksual pada pria dan wanita, mulai diketahui pada saat anak memasuki  masa pra pubertas. Untuk anak pria kelainan yang muncul seperti kriptorkismus, hipospadia, tidak adanya vas deferens bilateral kongenital, dan pseudohermafroditisme . Masa pra pubertas merupakan masa yang terjadi mengawali masa akhir kanak-kanak yang disebut dengan prapuber, disebut juga sebagai tahap pematangan dimana pada tahapan ini ciri-ciri seks sekunder mulai nampak dan organ-organ reproduksi pada anak pria sudah mulai berkembang sempurna. Untuk itu perlu pengenalan sejak dini melalui transfer pengetahuan menyangkut organ reproduksi, terutama diketahui oleh orang tua, sehingga bisa memperhatikan kondisi kesehatan anak dalam keluarga dan tentunya dapat menentukan langkah untuk penanggulangan sejak dini jika ditemukan adanya gangguan pada organ reproduksi anak. Mitra yang mengikuti kegiatan ini merupakan warga masyarakat di Kelurahan Meras Kecamatan Bunaken, yang memiliki anak-anak berusia pra pubertas sampai menginjak usia remaja. Tujuan kegiatan ini yaitu meningkatkan pengetahuan masyarakat tentang kesehatan reproduksi pada anak pria prapubertas. Hasil yang diperoleh yaitu adanya peningkatan pengetahuan lewat tes yang diberikan sebelum dan sesudah transfer ilmu, dan hasil pemeriksaan gratis yang dilakukan tidak ditemukan kelainan pada anak sampel.           Kata kunci: Gangguan; reproduksi; kriptorkismus; hipospadia; Meras